2008
DOI: 10.2344/0003-3006(2008)55[2:gtapsf]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Gow-Gates Technique: A Pilot Study for Extraction Procedures With Clinical Evaluation and Review

Abstract: The aim of this study was to compare the effectiveness of 2 different volumes of anesthetic solution for a premolar-molar extraction, and to determine the onset of complete mandibular conduction anesthesia via a Gow-Gates mandibular block. One operator performed 32 blocks with a 27-gauge needle on patients who required a dental extraction: 16 blocks using 1.8 mL of anesthetic solution, and 16 blocks using 3.6 mL of anesthetic solution. The parameters evaluated were frequency of successful anesthesia and onset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…Takeuchi (25), on the basis of a computed tomography scan study, reported an average volume of 1.27 AE 0.59 mL with the mouth closed and 1.99 AE 0.4 mL with the mouth opened. Some authors using the Gow-Gates technique have reported that volumes more than 1.8 mL produce better success rates than 1.8 mL of 2% lidocaine solution (16,26). Kohler et al (16) reported a significant increase in the success rate while using 3.6 mL of 2% lidocaine hydrochloride with 1:100,000 epinephrine as compared with 1.8 mL of the solution.…”
Section: Clinical Researchmentioning
confidence: 98%
See 1 more Smart Citation
“…Takeuchi (25), on the basis of a computed tomography scan study, reported an average volume of 1.27 AE 0.59 mL with the mouth closed and 1.99 AE 0.4 mL with the mouth opened. Some authors using the Gow-Gates technique have reported that volumes more than 1.8 mL produce better success rates than 1.8 mL of 2% lidocaine solution (16,26). Kohler et al (16) reported a significant increase in the success rate while using 3.6 mL of 2% lidocaine hydrochloride with 1:100,000 epinephrine as compared with 1.8 mL of the solution.…”
Section: Clinical Researchmentioning
confidence: 98%
“…Murphy and Grundy (15) estimated the volume of the pterygomandibular space to be approximately 2.0 mL. Kohler et al (16) suggested from a clinical observation that two 1.8-mL cartridges (3.6 mL) more adequately fill the pterygomandibular space. Madrid et al (17) reported that the ''volume of the pterygomandibular space is quite superior to the value usually reported in the dental literature.''…”
mentioning
confidence: 98%
“…한다 (Goldberg et al, 2008;Malamed, 2004;Waikakul and Punwutikorn, 1991). (Cohen et al, 1993Kohler et al, 2008Levy, 1981;Malamed, 1981;Montagnese et al, 1984;Sisk, 1985;Watson andGow-Gates, 1976 Zandi andSabounchi, 2008 …”
Section: ) 주사침 자입 시 통증이 거의 없다mentioning
confidence: 99%
“…Nevertheless, onset of anesthesia is slower in the GGB (five to ten minutes) in comparison with the IANB (7). Although some studies reported that the success rate of the GGB was more than the IANB (7,11,17,18), others showed that both techniques had the same success rate (20,21) and in some cases, the IANB had a higher success rate (19).…”
Section: Introductionmentioning
confidence: 99%